Fractional-order internal model control algorithm based on the force/position control structure of redundant actuation parallel robot. (7th January 2020) - Wen, Shuhuan; Hu, Xueheng; Zhang, Baowei; Sheng, Miao; Lam, HK; Zhao, Yongsheng
This article proposes a new control structure for the complex redundant actuation parallel robot based on force/position hybrid control structure. The traditional proportional–integral–derivative control method, integer-order internal model control method and fractional-filter internal model control–proportional–derivative control method are used in the position structure of force/position hybrid control. The fractional-filter internal model control–proportional–derivative control method is used in the position loop of the permanent magnet synchronous motor to reduce the position error. A fractional-order theory with the internal model control method is used in redundant actuation force control structure, which can improve the control precision of the driving force of the parallel robot. The Admas/Matlab simulation results show that the proposed method outperforms other methods and can obtain good robustness and tracking performance.